Dialogue and debate in psychology: Commentary on the foundational myth of psychology as a science - de Saint Laurent, Constance (Ontario: Captus, 2015)
This paper proposes to consider the discourses surrounding the “birth” of psychology, especially the stories around the Leipzig laboratory, as collective memory. It argues that analysing this ‘foundational myth’ of psychology may shed light on the current oppositions and divisions within the field. Seeing psychology as the product of an original and necessary separation between two distinct branches may indeed have sterilised the debate far beyond those who started it. Finally, drawing on dialogism and pragmatism, it considers that the recognition of the legitimacy of the knowledge of the other and the reopening of the epistemological debate are necessary steps towards the instauration of a fruitful dialogue within the field.
Keywords: history of psychology; collective memory